Vpliv izbora prostorske enote na rezultate geografskih statističnih analiz - Krevs, Marko (Geografski vestnik, 1998)
Presented are certain findings of an investigation about the effects of selecting spatial unit on the results of geographical statistical analyses and their explanation. Included into the discussion are 26 variables of the following subject fields; physico-geographical features, population, dwellings and settling pattern, economy and employment, agriculture and farming lands, incomes and spatial accessibility. Analysed were the data for entire Slovenia, gathered by the following areas (i.e., spatial units): local communities, municipalities, administrative-unit areas, physico-geographical regions, economico-geographical regions and regional planning communities. The effect of selecting spatial units is assessed through the comparison of results of different methods: descriptive statistics, correlation analysis, multiple regression analysis, and principal components analysis. Numerous results change when spatial units are changed which is in accordance with our anticipations based on a premise that correlation exists between the area size and the results of the results of analyses. Yet, a significant percentage of results deviate from these anticipations. In some cases, it is possible to obtain on the basis of correlation analysis even the controversial findings for the same area when using different spatial units. Therefore, it is necessary to pay attention at the explanation of results also on the possible effects of the size of spatial units and the mode of their determination, according to which the data are aggregated.
Keywords: geografija; geography; metodologija; Slovenia; Slovenija; statistična analiza; statistične metode; statistični podatki